Microleakage of Nanofiller Resin Composite, Glass Ionomer Cement and Resin Modified Glass Ionomer Cement in Class V Cavities - Sania Wahyuanafi Arstiara; Dwi Warna Aju Fatmawati; Raditya Nugroho (Pustaka Kesehatan, 2022)
Class V cavity is cavity happened in a third of anterior or posterior teeth cervix that can be restored with resin composite, glass ionomer cement, and resin modified glass ionomer cement. Discoloration is often seen in the marginal of the filling that caused by microleakage. The purpose of the study is to find out aesthetic restoration microleakage in class V cavity. This study type is laboratory experimental research. There are 12 samples of maxillary premolar which were prepared for class V cavity. Group I restored with resin composite (n=4), group II restored with glass ionomer cement (n=4) and group III restored with resin modified glass ionomer cement (n=4). Furthermore, premolar teeth that have been filled soaked into methylene blue solution for 24 hours at 37°C. The microleakage value is measured based on the penetration depth of methylene blue solution at the marginal of the cavity. The average calculation of microleakage in sequence is resin modified glass ionomer cement, glass ionomer cement, and resin composite. The conclusions of this study prove that there is significant difference in microleakage value of each group samples. Keyword: Class V cavity, Microleakage, Resin composite, Glass ionomer cement, Resin modified glass ionomer